Macroparasite communities in European eels, Anguilla anguilla, from French Mediterranean lagoons, with special reference to the invasive species Anguillicola crassus and Pseudodactylogyrus spp. - G. Fazio; P. Sasal; R. Lecomte-Finiger; C. Da Silva; B. Fumet; H. Moné (Knowledge and Management of Aquatic Ecosystems, 2008)
European eel parasites, in particular invasive species, are suspected to play a role in the decline in the populations of their host. The aims of this work were to describe the parasitic fauna of eels in French Mediterranean lagoons and to study the epidemiological trends of the invasive helminth species, the nematode Anguillicola crassus and the monogenean Pseudodactylogyrus spp., in regard to spatio-temporal dynamics, host biological characteristics and parasite community. A total of 418 eels was sampled in eight lagoons between March 2003 and June 2005. Our results revealed a total macroparasite richness of 23 species: 1 Monogenea, 13 Digenea, 2 Cestoda, 3 Nematoda, 2 Acantocephala and 2 Crustacea. We found no variation in A. crassus abundance in Salses-Leucate lagoon in the same month across years. However, the nematode abundance was higher in eels caught in summer than in those caught in winter. Pseudodactylogyrus sp. was not found in Salses-Leucate lagoon, except in July 2004. Comparisons between the lagoons on the same date showed that they could be separated into two groups for both species' abundance: Grau-du-Roi, Mauguio, Palavas and Vaccarès lagoons, where abundance was rather high, against Bages-Sigean, Pierre-Blanche, Salses-Leucate and Thau lagoons, where abundance was rather low or nil. We found significant negative relationships between A. crassus abundance and the length and age of eels. We also found a significant positive relationship between A. crassus and Pseudodactylogyrus sp. abundance. Finally, our results showed significant positive relationships between both A. crassus and Pseudodactylogyrus sp. abundance and the abundance of the digeneans Prosorhynchus aculeatus and Lecithochirium gravidum. We discuss the results in regard to the dynamics of invasions, the characteristics of the parasite life cycles and the ecology of eels.